Pola Internalisasi Nilai Keislaman Keluarga Muhammadiyah Dan Islam Abangan - Surawan Surawan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Family is a very effective school in instilling the value of internalization. For this reason, the purpose of this study are 1) What is the diversity of Muhammadiyah and Islam Abangan families? 2). What is the pattern of internalization of Islamic values ​​that occurs in the family of Muhammadiyah and Islam Abangan? 3). What is the problem encountered in the effort to internalize Islamic values ​​and what is the solution to overcome it? This study used a qualitative descriptive design with a research cite in the Kulon Progo Regency Kokap District. The research subjects consisted of 5 main families in the Head of Muhammadiyah Hargomulyo consisted of 3 Muhammadiyah families and 2 Muslim families of Abangan Hargomulyo. The research method used interview, observation and documentation while data analysis used reduction, display and verification. The results of this study were 1). The religious diversity of the Muhammadiyah and Abangan families in principle has similarities, both Muhammadiyah and Abangan, faithfully believe in God. Only in the Abangan family did the belief system occur syncretism between the teachings of Islam and the culture of anismism, Hinduism and Buddhism. In prayer worship activities, most Abangan families did not carry out Islam faithfully, for the implementation of fasting was same, only Abangan families knew a number of fasts that the Prophet had never taught. In the activity of family charity, the abangan family did a lot of slametan, while Muhammadiyah did not. For social issues, both Muhammadiyah and Abangan there was no difference. 2). The pattern of internalization of religious values ​​included material internalization in the creed (faith), worship and morals. The method used in the internalization process was indoctrination, exemplary and habitual behavior. 3). The problems of internalizing religious values ​​included parenting, the level of children's association, technological advances and bustle, caused communication patterns to be constrained